2021
DOI: 10.3390/microbiolres12020026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Environments of Plasmid-Mediated blaCTXM-15 Beta-Lactamase Gene in Enterobacteriaceae from Africa

Abstract: The most widely distributed blaCTX-M gene on a global scale is blaCTX-M-15. The dissemination has been associated with clonal spread and different types of mobile genetic elements. The objective of this review was to describe the genetic environments of the blaCTX-M-15 gene detected from Enterobacteriaceae in published literature from Africa. A literature search for relevant articles was performed through PubMed, AJOL, and Google Scholar electronic databases; 43 articles from 17 African countries were included… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
(127 reference statements)
1
16
0
Order By: Relevance
“…In contrast to the IncFIB plasmids described above, p786605 (IncI1 plasmid) encoded several AMR determinants ( dfrA1, aadA1, bla TEM , sul2 and qnrS1 ) in addition to bla CTX-M-15 . MDR bla CTX-M-15 -encoding plasmids have been identified in previous literature but are most commonly associated with IncFII-FIA-FIB plasmid replicons ( Awosile and Agbaje, 2021 ; Minja et al, 2021 ). Analysis also identified the intI1 gene, suggesting the presence of a class 1 (C1) integron ( Ghaly et al, 2017 ; Awosile and Agbaje, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the IncFIB plasmids described above, p786605 (IncI1 plasmid) encoded several AMR determinants ( dfrA1, aadA1, bla TEM , sul2 and qnrS1 ) in addition to bla CTX-M-15 . MDR bla CTX-M-15 -encoding plasmids have been identified in previous literature but are most commonly associated with IncFII-FIA-FIB plasmid replicons ( Awosile and Agbaje, 2021 ; Minja et al, 2021 ). Analysis also identified the intI1 gene, suggesting the presence of a class 1 (C1) integron ( Ghaly et al, 2017 ; Awosile and Agbaje, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…MDR bla CTX-M-15 -encoding plasmids have been identified in previous literature but are most commonly associated with IncFII-FIA-FIB plasmid replicons ( Awosile and Agbaje, 2021 ; Minja et al, 2021 ). Analysis also identified the intI1 gene, suggesting the presence of a class 1 (C1) integron ( Ghaly et al, 2017 ; Awosile and Agbaje, 2021 ). Comparison to the general structure of C1 integrons outlined by Kubomura et al (2020) showed p786605 contains a truncated C1 integron encoding dfrA1 , aadA1 & bla TEM .…”
Section: Resultsmentioning
confidence: 99%
“…CTX-M-15 is the most widely distributed bla CTX-M gene on a global scale among Enterobacteriaceae, it has been associated with other ESBLs including carbapenemase and also with colistin resistance determinants (Ribeiro et al 2016;Zeynudin et al 2018;Soliman et al 2020;Awosile and Agbaje 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The global emergence of ESBLs represents one of the greatest public health threats in hospitals, and bla CTX-M-15 is the most common ESBL gene distributed globally in different clinical strains of Enterobacteriaceae (Rossolini et al 2008;Sewunet et al 2021;Awosile and Agbaje 2021) including Enterobacter spp. (Haenni et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Three K. pneumoniae isolates (ST395 K47 , ST147 K64 , and ST23 K1 ) carried the bla TEM-1B , bla CTX-M-15 , and bla OXA-1 genes. It was reported that these genes were horizontally transferred by the IncFIA-FIB-FII and IncHI2 plasmids [ 37 , 38 ]. One isolate (ST23 K57 ) carried the bla CTX-M-55 and bla OXA-1 genes; such gene combination was reported previously from China [ 39 ].…”
Section: Discussionmentioning
confidence: 99%